Financial and managerial accounting - Warren, Carl S. (South-Western College, 1999)
This book is about: Analyzing transaction; The matching concept and the adjusting process; Completing the accounting cycle; Accounting for merchandising; Accounting systems, Internal controls, and cash; ...